FCC gasoline hydro-upgrading desulfurization catalyst and preparation method thereof
The prepared FCC gasoline hydrotreating desulfurization catalyst, by combining modified nano ZSM-5 molecular sieve and metal oxide, achieves the effect of simultaneous desulfurization and olefin reduction in FCC gasoline, solving the economic loss problem of gasoline standard upgrade in the existing technology and meeting the requirements of China VI gasoline.
Patent Information
- Application Number
- CN202311419211.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-30
- Publication Date
- 2025-11-25
- Estimated Expiration
- 2043-10-30
AI Technical Summary
Existing technologies cannot maintain or increase the octane rating of gasoline while reducing the sulfur and olefin content of FCC gasoline, resulting in economic losses when meeting the China VI gasoline standard.
The FCC gasoline hydrotreating and desulfurization catalyst prepared by extrusion molding contains a reforming component, a selective desulfurization component, and a binder. It achieves isomerization, aromatization, and cyclization reactions through a combination of modified nano ZSM-5 molecular sieves and metal oxides or salts, thereby reducing olefin content and increasing octane number.
It achieves a significant reduction in sulfur and olefin content in FCC heavy gasoline, while increasing the octane number to meet the China VI gasoline standard. The product's sulfur content is reduced to 3-10 ppm, olefin content to 9-14 v%, octane number is increased by 0.1-3 units, and gasoline yield is 98-99%.
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of clean gasoline production catalysts, and relates to an FCC gasoline hydro-upgrading desulfurization catalyst and a preparation method thereof. BACKGROUND
[0002] With the continuous improvement of people's health consciousness, the requirement for air quality is also upgraded, and China has introduced more stringent gasoline quality standards, and the national VI gasoline standard (sulfur < 10 mg / kg) is implemented since January 1, 2019. The most significant change of the national VI gasoline standard is the substantial reduction of the olefin content (national VlA stage: olefin content < 18 v% before 2023; national VIB stage: olefin content < 15 v% after 2023). However, the composition of gasoline in China is mainly FCC gasoline components, which generally accounts for about 70% of the gasoline pool. The FCC gasoline has high olefin content and high sulfur content. Therefore, the national VI gasoline quality upgrading in China needs to reduce both the olefin content and the sulfur content of gasoline.
[0003] At present, clean gasoline production technologies include: 1) represented by the Prime G+ technology of Axens, the PHG of China Petroleum and the S-Zorb technology of China Petrochemical, mainly through hydrodesulfurization, and the reduction of olefins is also through the hydrogenation reaction to make the olefins saturated into alkanes. Such technology will cause a large loss of gasoline octane number, and other high octane components need to be blended to make up for the octane number. At the same time, the reaction process is prone to cause large heat release due to the saturation of a large amount of olefins, which is not easy to control; 2) represented by the M-PHG / Gardes technology of the modification-desulfurization / desulfurization-modification technology, first, the olefins are converted into high-octane isomeric alkanes, aromatic hydrocarbons and other components through isomerization and aromatization catalysts, and then the gasoline is cleaned through selective desulfurization. These processes are mostly desulfurization or modification combined technologies for FCC heavy gasoline (S-Zorb technology is full-range feed), in order to achieve both desulfurization and olefin reduction, and reduce the loss of octane number, 2-3 kinds of catalysts need to be used to achieve the purpose of clean gasoline. Under the condition of meeting the national VlA, the octane number of clean gasoline will still be lost by 0.5-2.0 units, causing great economic loss to the refinery. A catalyst and a preparation method thereof capable of deeply desulfurizing and greatly reducing the olefins of FCC heavy gasoline while improving the octane number have not been reported. SUMMARY
[0004] In order to overcome the deficiencies of the prior art, the application provides an FCC gasoline hydro-upgrading desulfurization catalyst and a preparation method thereof. The catalyst prepared by the preparation method has both modification and desulfurization performances, meets the requirements of the national VI gasoline quality, and improves the octane number.
[0005] The above object of the application is achieved by the following technical scheme:
[0006] The FCC gasoline hydro-upgrading desulfurization catalyst comprises a modification component, a selective desulfurization component and a binder.
[0007] The preparation method of the FCC gasoline hydro-upgrading desulfurization catalyst comprises the following steps: molding by using an extrusion molding method, drying, calcining and reducing to obtain the finished catalyst.
[0008] The preparation method specifically comprises the following steps: drying the raw material modification component, the selective desulfurization component and the binder in a flowing air atmosphere at 80-120 DEG C, calcining the raw material modification component, the selective desulfurization component and the binder in a flowing air atmosphere at 400-500 DEG C, and reducing the raw material modification component, the selective desulfurization component and the binder in a H2 atmosphere at 300-500 DEG C for 2-4 h to obtain the finished catalyst.
[0009] The modification component is prepared by using a nano ZSM-5 molecular sieve modification method, and the nano ZSM-5 molecular sieve has a particle size of 20-150 nm, preferably 30-90 nm.
[0010] The selective desulfurization component is any two or more oxides or salts in Cr, Mo, W, Fe, Co, Ni, Zn, Al and Si, which are prepared into oxide powders by physical mixing or a coprecipitation method, and the selective desulfurization component has a nano high specific surface structure, and the specific surface is 10-200 m 2 / g.
[0011] The binder is any one or a mixture of two or more of pseudo-boehmite, silica sol, cellulose, polyvinyl alcohol and cyclodextrin, which is mixed with water or acid water.
[0012] The molecular sieve modification method comprises a method for adjusting the acidity of the molecular sieve by hydrothermal treatment, acid treatment, ion exchange, silanization and metal impregnation, and the modified molecular sieve has reasonable L acid and B acid, so that the effect of reducing olefins and improving octane number of the catalyst is ensured.
[0013] The preparation of the modification component specifically comprises the following steps: taking H-type ZSM-5 molecular sieve with a particle size of 30-50 nm, performing hydrothermal treatment at 500 DEG C for 4 h, adding any one of Fe, Zr and Ti salt solutions to perform ion exchange, filtering the ion exchange solution to obtain a filter cake, drying the filter cake at 120 DEG C and calcining the filter cake at 400 DEG C to obtain the modification component powder.
[0014] The catalyst prepared by using the preparation method is used in the application of FCC heavy gasoline hydro-upgrading desulfurization reaction.
[0015] Compared with the prior art, the FCC gasoline hydro-upgrading desulfurization catalyst has the following beneficial effects:
[0016] The application provides an FCC gasoline hydro-upgrading desulfurization catalyst and a preparation method thereof.
[0017] The catalyst prepared by the preparation method is used for an FCC heavy gasoline up-grading desulfurization reaction, can greatly selectively desulfurize, and can reduce olefins through isomerization, aromatization, cyclization and other up-grading reactions, so that the olefins are reduced to 9-14 v%, the product octane number is increased by 0.1-3 units, the product sulfur content is reduced to 3-10 ppm, the gasoline yield is 98-99%, and the gasoline VI B sulfur and olefin requirements are fully met. DETAILED DESCRIPTION
[0018] The application will be described in detail below through specific examples, but the protection scope of the application is not limited. Unless otherwise specified, the experimental methods used in the application are conventional methods, and the experimental apparatus, materials and reagents used can be obtained from commercial channels.
[0019] Example 1
[0020] 1) Upgrading component preparation: 30-50 nm H-type ZSM-5 molecular sieve was taken, hydrothermally treated at 500 DEG C for 4 h, ion exchanged by adding iron nitrate solution, and the filter cake was obtained after filtration, the filter cake was dried at 120 DEG C and calcined at 400 DEG C to obtain the upgrading component powder A;
[0021] 2) Selective desulfurization component preparation: according to the mass ratio MoO3: CoO = 6:1, ammonium heptamolybdate and cobalt nitrate were weighed, dissolved in ammonia water, heated and co-precipitated, the precipitate was washed and filtered to obtain the filter cake, the filter cake was dried at 120 DEG C and calcined at 400 DEG C to obtain the selective desulfurization component B;
[0022] 3) Binder preparation: according to the mass ratio Al2O3: SiO2: cellulose: HNO3: H2O = 10:20:3:0.5:50, pseudo-boehmite, silica sol, cellulose, concentrated HNO3 and pure water (the water in pseudo-boehmite, silica sol and concentrated HNO3 is deducted) were weighed and mixed uniformly to obtain the binder C, and the dry basis content was calculated.
[0023] 4) Catalyst product preparation: A, B and C were weighed according to the dry basis content A:B:C = 85:5:10, mixed uniformly in a kneading machine, extruded by an extruder to obtain a shaped strip, the shaped strip was dried at 120 DEG C for 8 h, calcined at 500 DEG C for 4 h, and reduced by H2 at 500 DEG C for 4 h to obtain the finished product.
[0024] Example 2
[0025] 1) modified component preparation: take the particle size of H type ZSM-5 molecular sieve of 30-50 nanometer, hydrothermal treatment at 500 DEG C for 4h, add iron nitrate solution for ion exchange, after exchange, washing, filtering, filter cake, filter cake 120 DEG C drying, 400 DEG C calcination modified component powder A is obtained;
[0026] 2) selective desulfurization component preparation: according to the mass ratio of MoO3: CoO = 6:1, take the ammonium heptamolybdate and cobalt nitrate, dissolve in ammonia, heat co-precipitation, the precipitate is filtered and washed to obtain the filter cake, the filter cake is dried at 120 DEG C and calcined at 400 DEG C to obtain the selective desulfurization component B;
[0027] 3) binder preparation: according to the mass ratio of Al2O3: polyvinyl alcohol: cyclodextrin: HNO3: H2O = 15:2:3:0.5:50, take pseudo-boehmite, polyvinyl alcohol: cyclodextrin, concentrated HNO3, pure water (pure water needs to deduct the water in pseudo-boehmite, silica sol, concentrated HNO3), mix evenly to obtain binder C, and calculate the dry basis content.
[0028] 4) catalyst finished product preparation: according to the dry basis content A:B:C = 85:5:10, A, B, C is taken, mixed evenly in the kneader, extruded into a shaped strip by the extruder, the shaped strip is dried at 120 DEG C for 8h, calcined at 500 DEG C for 4h, reduced by H2 at 500 DEG C for 4h to obtain the finished product.
[0029] Example 3
[0030] 1) modified component preparation: take the particle size of H type ZSM-5 molecular sieve of 30-50 nanometer, hydrothermal treatment at 500 DEG C for 4h, add iron nitrate solution for ion exchange, after exchange, washing, filtering, filter cake, filter cake 120 DEG C drying, 400 DEG C calcination modified component powder A is obtained;
[0031] 2) selective desulfurization component preparation: according to the mass ratio of NiO: Fe2O3: Al2O3 = 1:9:90, take the basic nickel carbonate, iron hydroxide and pseudo-boehmite, mix evenly to obtain the selective desulfurization component B;
[0032] 3) binder preparation: according to the mass ratio of polyvinyl alcohol: cyclodextrin: cellulose: HNO3: H2O = 1:2:3:0.5:50, take pseudo-boehmite, silica sol, cellulose, concentrated HNO3, pure water (pure water needs to deduct the water in pseudo-boehmite, silica sol, concentrated HNO3), mix evenly to obtain binder C, and calculate the dry basis content.
[0033] 4) catalyst finished product preparation: according to the dry basis content A:B = 50:50, A, B is taken, mixed evenly in the kneader, add C appropriately, extruded into a shaped strip by the extruder, the shaped strip is dried at 120 DEG C for 8h, calcined at 500 DEG C for 4h, reduced by H2 at 500 DEG C for 4h to obtain the finished product.
[0034] Example 4
[0035] 1) Preparation of modified component: Take H-type ZSM-5 molecular sieve with a particle size of 30-50 nanometers, perform acid treatment at room temperature for 4 hours, add a nickel nitrate solution for ion exchange, wash and filter after the exchange to obtain a filter cake, dry the filter cake at 120°C, and calcine at 400°C to obtain modified component powder A;
[0036] 2) Preparation of selective desulfurization component: Take Cr2O3 and cobalt nitrate according to a mass ratio of Cr2O3:CoO = 5:1, immerse Cr2O3 in a cobalt nitrate aqueous solution, filter to obtain a filter cake, dry the filter cake at 120°C, and calcine at 400°C to obtain selective desulfurization component B;
[0037] 3) Preparation of binder: Take pseudoboehmite, silica sol, cellulose, concentrated HNO3, and pure water (the water in the pseudoboehmite, silica sol, and concentrated HNO3 is deducted from the pure water) according to a mass ratio of Al2O3:SiO2:cellulose:HNO3:H2O = 10:20:3:0.5:50, mix uniformly to obtain binder C, and calculate the dry basis content.
[0038] 4) Preparation of finished catalyst: Take A, B, and C according to a dry basis content of A:B:C = 40:40:20, mix uniformly in a kneader, extrude through an extruder to obtain a shaped strip, dry the shaped strip at 120°C for 8 hours, calcine at 500°C for 4 hours, and reduce at 500°C in H2 for 4 hours to obtain the finished product.
[0039] Example 5
[0040] 1) Preparation of modified component: Take H-type ZSM-5 molecular sieve with a particle size of 30-50 nanometers, perform hydrothermal treatment at 600°C for 4 hours, add a zinc nitrate solution for ion exchange, filter after the exchange to obtain a filter cake, dry the filter cake at 120°C, and calcine at 400°C to obtain modified component powder A;
[0041] 2) Preparation of selective desulfurization component: Take ammonium metatungstate and water glass according to a mass ratio of WO3:SiO2 = 1:6, stir and mix uniformly, add dilute nitric acid for co-precipitation, filter and wash the precipitate to obtain a filter cake, dry the filter cake at 120°C, and calcine at 400°C to obtain selective desulfurization component B;
[0042] 3) Preparation of binder: Take pseudoboehmite, silica sol, cellulose, concentrated HNO3, and pure water (the water in the pseudoboehmite, silica sol, and concentrated HNO3 is deducted from the pure water) according to a mass ratio of Al2O3:SiO2:cellulose:HNO3:H2O = 10:20:3:0.5:50, mix uniformly to obtain binder C, and calculate the dry basis content.
[0043] 4) Catalyst product preparation: A, B, C were weighed according to the dry basis content A: B: C = 85:5:10, mixed uniformly in a kneader, extruded into a shaped strip by an extruder, and the shaped strip was dried at 120°C for 8h, calcined at 500°C for 4h, and reduced by H2 at 500°C for 4h to obtain the product.
[0044] Example 6
[0045] 1) Modified component preparation: H-type ZSM-5 molecular sieve with a particle size of 30-50 nanometers was hydrothermally treated at 500°C for 4h, and silanized by using trimethylethoxysilane. The filter cake was obtained by filtration and washing, and the modified component powder A was obtained by drying the filter cake at 120°C and calcining at 400°C.
[0046] 2) Selective desulfurization component preparation: ammonium heptamolybdate and zinc carbonate were weighed according to the mass ratio of MoO3: ZnO = 1:20, mixed uniformly to obtain the selective desulfurization component B.
[0047] 3) Binder preparation: pseudoboehmite, silica sol, cellulose, concentrated HNO3, and pure water (the water in pseudoboehmite, silica sol, and concentrated HNO3 should be deducted) were weighed according to the mass ratio of Al2O3: SiO2: cellulose: HNO3: H2O = 10:20:3:0.5:50, mixed uniformly to obtain the binder C, and the dry basis content was calculated.
[0048] 4) Catalyst product preparation: A, B, C were weighed according to the dry basis content A: B: C = 85:5:10, mixed uniformly in a kneader, extruded into a shaped strip by an extruder, and the shaped strip was dried at 120°C for 8h, calcined at 500°C for 4h, and reduced by H2 at 500°C for 4h to obtain the product.
[0049] Example 7
[0050] 1) Modified component preparation: H-type ZSM-5 molecular sieve with a particle size of 50-70 nanometers was hydrothermally treated at 500°C for 4h, and ion exchanged by adding iron nitrate solution. The filter cake was obtained by filtration, and the modified component powder A was obtained by drying the filter cake at 120°C and calcining at 400°C.
[0051] 2) Selective desulfurization component preparation: ammonium heptamolybdate and zinc carbonate were weighed according to the mass ratio of MoO3: ZnO = 1:20, mixed uniformly to obtain the selective desulfurization component B.
[0052] 3) Binder preparation: pseudoboehmite, silica sol, cellulose, concentrated HNO3, and pure water (the water in pseudoboehmite, silica sol, and concentrated HNO3 should be deducted) were weighed according to the mass ratio of Al2O3: SiO2: cellulose: HNO3: H2O = 10:20:3:0.5:50, mixed uniformly to obtain the binder C, and the dry basis content was calculated.
[0053] 4) Catalyst product preparation: A, B, C were weighed according to the dry basis content A:B:C = 85:5:10, mixed uniformly in a kneader, extruded into a shaped strip by an extruder, the shaped strip was dried at 120℃ for 8h, calcined at 500℃ for 4h, reduced by H2 at 500℃ for 4h to obtain the product.
[0054] Example 8
[0055] 1) Modified component preparation: H-type ZSM-5 molecular sieve with a particle size of 70-90 nanometers was hydrothermally treated at 500℃ for 4h, then ion exchanged by adding a ferric nitrate solution, and the exchanged product was filtered to obtain a filter cake, which was dried at 120℃ and calcined at 400℃ to obtain modified component powder A;
[0056] 2) Selective desulfurization component preparation: ammonium heptamolybdate and zinc carbonate were weighed according to the mass ratio MoO3:ZnO = 1:20, mixed uniformly to obtain selective desulfurization component B;
[0057] 3) Binder preparation: pseudo-boehmite, silica sol, cellulose, concentrated HNO3, and pure water (the water content in pseudo-boehmite, silica sol, and concentrated HNO3 was deducted) were weighed according to the mass ratio Al2O3:SiO2:cellulose:HNO3:H2O = 10:20:3:0.5:50, mixed uniformly to obtain binder C, and the dry basis content was calculated.
[0058] 4) Catalyst product preparation: A, B, C were weighed according to the dry basis content A:B:C = 85:5:10, mixed uniformly in a kneader, extruded into a shaped strip by an extruder, the shaped strip was dried at 120℃ for 8h, calcined at 500℃ for 4h, reduced by H2 at 500℃ for 4h to obtain the product.
[0059] The catalytic effects of the catalysts prepared in Examples 1-8 of the present application were evaluated and tested on a 100ml pilot evaluation device using FCC heavy gasoline as the raw material.
[0060] Test Example
[0061] The catalysts prepared in Examples 1-8 above were respectively loaded in the reactor of the pilot device, and after passing the air tightness test, the hydrogen partial pressure was adjusted to 1.0MPa, the hydrogen to oil ratio was 300 (according to the space velocity 1.5h -1 ), the temperature was raised to 350℃ at a rate of 30℃ / h, the raw oil was fed (space velocity 1.5h -1 ), the temperature and oil amount were stabilized, the temperature was raised to 380℃ at a rate of 20℃ / h, and the temperature was kept constant for 12h, the sample was analyzed for S, composition, and octane number (RON). The test results are shown in Table 1
[0062] Table 1 Test results of the catalysts prepared in Examples
[0063] Cat. No. S / ppm RON % recovery Aromatics Olefins Saturates ΔRON Feed oil 151.54 85.1 - 27.9 24.1 48.0 - Example 1 7.94 86.8 98.1 30.6 10.3 59.1 1.7 Example 2 3.64 85.9 98.4 30.0 11.2 58.8 0.8 Example 3 3.58 85.4 98.4 29.9 11.8 58.3 0.3 Example 4 2.12 85.2 98.5 29.8 13.6 56.6 0.1 Example 5 7.19 86.7 98.7 30.1 12.4 57.5 1.6 Example 6 3.34 85.4 98.2 29.8 13.9 56.3 0.3 Example 7 5.16 86.2 98.6 30.5 9.1 60.4 1.1 Example 8 9.06 87.2 98.9 31.0 11.1 57.9 2.1
[0064] The above-described embodiments are merely preferred embodiments of the present application, but are not all the possible embodiments of the present application. Any modification of the above-described embodiments that can be obvious to those skilled in the art without departing from the spirit and technical scope of the present application should be considered to fall within the scope of the present application.
Claims
1. An FCC gasoline hydro-upgrading desulfurization catalyst characterized by, The modified component, the selective desulfurization component, and the binder; the dry mass percentage of the modified component, the selective desulfurization component, and the binder is 40-85%:5-60%:0-20%; The preparation of the modified component is specifically as follows: taking H-type ZSM-5 molecular sieve with a particle size of 30-90 nanometers, performing hydrothermal treatment at 500 DEG C or 600 DEG C for 4 hours, adding a solution of any one of Fe, Zr, and Ti salt to perform ion exchange, filtering the exchanged product to obtain a filter cake, drying the filter cake at 120 DEG C, and calcining the filter cake at 400 DEG C to obtain a modified component powder; The selective desulfurization component is any two or more oxides or salts of Cr, Mo, W, Fe, Co, Ni, Zn, Al, Si prepared by physical mixing or coprecipitation method into oxide powder, the selective desulfurization component is nano high specific surface structure, the specific surface is 10-200m 2 / g; The preparation method of the FCC gasoline hydro-upgrading desulfurization catalyst is as follows: using an extrusion molding method to form, drying, calcining, and reducing to obtain the finished catalyst.
2. The FCC gasoline hydro upgrading desulfurization catalyst of claim 1, wherein the FCC gasoline hydro upgrading desulfurization catalyst is characterized by, The raw material modified component, the selective desulfurization component, and the binder are dried at 80-120 DEG C in a flowing air atmosphere, calcined at 400-500 DEG C in a flowing air atmosphere, and reduced at 300-500 DEG C in an H2 atmosphere for 2-4 hours to obtain the finished catalyst.
3. The FCC gasoline hydro upgrading desulfurization catalyst of claim 1, wherein the FCC gasoline hydro upgrading desulfurization catalyst is characterized by, The binder is any one of pseudo-boehmite, silica sol, cellulose, polyvinyl alcohol, cyclodextrin, or a mixture of two or more thereof, and water or acid water.
4. The use of the FCC gasoline hydro-upgrading desulfurization catalyst according to any one of claims 1-3 in the FCC heavy gasoline upgrading desulfurization reaction.
Citation Information
Patent Citations
Hydrogenation reforming method for inferior gasoline
CN102295955A
Desulfurization catalyst for hydrocarbon oil, preparation method of desulfurization catalyst and method for desulfurizing hydrocarbon oil
CN105214715A